The seven deadly sins of white Christian nationalism a call to action - Heyward, Carter 1945- (Blue Ridge Summit Rowman & Littlefield Publishers, Incorporated, 2022)
As right-wing conservatives dare to call themselves Christians while tearing down equality and justice and fanning the flames of fascism in America, Carter Heyward issues a call to action for true lovers of God. Only by condemning the destructive culture of white Christian nationalism can we fashion a world full of God's truth, love, and wisdom.
Cover -- Contents -- Acknowledgments -- Preface -- In the Beginning -- Why This Book? -- What Is White Christian Nationalism? -- The Seven Deadly Sins -- Sin as Our Collective Problem -- The First Sin -- The Second Sin -- The Third Sin -- The Fourth Sin -- The Fifth Sin -- The Sixth Sin -- The Seventh Sin -- A Call to Action -- Questions and Call -- The First Call -- The Second Call -- The Third Call -- The Fourth Call -- The Fifth Call -- The Sixth Call -- The Seventh Call -- Notes -- Resources and Selected Bibliography -- Index -- About the Author.
"Hear the call to overcome today's conservative rhetoric of hate and bring virtue back to Christian living... While right-wing conservatives dare to call themselves Christians as they tear down equality and justice, commit horrible acts of violence, and fan the flames of fascism in America, Carter Heyward issues a call to action for Christians to truly hear God's message of peace and love. This book attempts to show ways in which, through our highly privatized theologies and personal spiritualities, we American Christians have played a major role in building and securing structures of injustice in American life. Rising tides of white supremacy, threats to women's reproductive freedoms and to basic human rights for gender and sexual minorities, the widening divide between rich and poor, and increasing natural disasters and the extinction of Earth's species all point to a world crying out for God's wisdom. To move forward as followers of Jesus, we must first call out these ingrained cultural attitudes for what they are-the seven deadly sins of white Christian nationalism. We must commit ourselves to building a more perfect union in small personal ways and in large public acknowledgment of what the culture of white Christian nationalism is doing to our country and world"--
Description based on publisher supplied metadata and other sources
Keywords: Christians, White -- United States; White nationalism -- United States; Christian conservatism -- Political aspects -- United States; Religious Right -- United States; Christianity and politics -- United States; Christianity and politics-United States